(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2024)
Background: Urethro-cutaneous fistula (UCF) after hypospadias surgery occurs regardless of the location of the meatus, procedure performed or experience of the surgeon. Hypospadias repair continues to be a singularly demanding form of surgical expression with considerable artistic latitude. The commonest complication of hypospadias surgery is fistula formation, which almost always requires repeat and similarly demanding surgery. Aims and Objectives: The aim of our study was to compare the result between simple and layered repair of UCF developing after hypospadias surgery. Materials and Methods: This comparative type of study was carried out in the Department of Paediatric Surgery, BSMMU, Dhaka from June 2015 to August 2016 for a period of 15 (fifteen) months. Forty (40) diagnosed cases of UCF were included in the study. All the participants were randomized into two groups named Group A & Group B. Group A was assigned to the simple repair technique & Group B was assigned to the layered repair technique. Relevant data were collected in a predesigned questionnaire. Results: The recurrent fistula formation rate was much higher in Group A (30%) than in Group B (05%), which was statistically significant in between the two groups. The majority of the fistulae recurred within a few days of the removal of the stent (from 7th to 10th POD). 6, out of 7 recurrent UCF were observed in this period. No recurrent fistula was observed beyond 4 weeks after operation. Conclusions: This study revealed that, the layered repair technique, with the addition of vascularized dorsal dartos fascia reduces the recurrent fistula formation rate in a significant number. Though more time consuming and technically difficult, we recommend wide application of layered repair technique in the management of post hypospadias UCF. Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 37-42